P1-S2.51 Sexually transmitted HCV in MSM in Montreal. (10th July 2011) - Thomas, R; Vezina, S; Machouf, N; O'Brien, R; Huchet, E; Longpré, D; Lavoie, S; Milne, M; Asselin, F; Trottier, B
Abstract : Methods: A retrospective analysis of the clients who attend the "Gay Screening Clinic" (GSC) at Clinique medical l'Actuel (Montreal, Canada) between May 2009 and April 2010 was conducted. Results: Among the 1010 patients included in the analyses we found five cases of new HCV infection which seems to be acquired by sexual transmission. All of them were male and MSM, none of the cases had previous history of IDU, but three reported having had sexual relation with IDU partners. All of them were previously vaccinated for Hepatitis A and B and screened for HIV. None of them were coinfected with HIV, but one was coinfected with Syphilis and one with Gonorrhoea. Patients infected with HCV were older than non HCV patients (37 years vs 32 years) and had a higher number of sexual partners during the last 12 months (16 part. vs 9 for the non HCV patients). One of the HCV cases reported not having anal intercourse, two reported having had occasional unprotected anal intercourse and two reported always using condom for anal intercourse. Conclusions: As in other urban centers, cases of sexually transmitted HCV had also been found in Montreal. This prevalence of 0.5% is very low compared to our HIV population in which the prevalence of sexually transmitted HCV is 3%. The particularity of MSM with recently acquired HCV by sexual transmission seems to be related to their engagement in sexual relation with high number of concurrent partners.